Nationwide surveillance of pESI-positive Salmonella Infantis ST32 in South Korea: Endemic establishment of a dominant lineage across the broiler production chain, 2020–2023 - Hee-Seung Kang; Md.Sekendar Ali; Bo-Youn Moon; Min Young Kim; Yu-Jeong Hwang; Ji-In Kim; Seung-Chun Park; Jae-Myung Kim; Suk-Kyung Lim (Food Microbiology, 2027)

Occupational risk assessment of p-tert-butylphenol: toxicity reference values and worker exposure evaluation - In Jae Bang; Ji Hyun Yu; Jung Eun Lim; Yubin Han; Yerim Koo; Damee Eun; Daeyeop Lee; Ig-Chun Eom; Ha Ryong Kim (Toxicological Research, 2026)

The C2H2-type zinc finger protein SlHair5 acts as a regulatory node coordinating trichome development and leaf morphogenesis in tomato - Seong-Min Kim; Jiyoung Kim; Jae-In Chun; Jang-Kyun Seo; Choonkyun Jung; Jin-Ho Kang (Plant Cell Reports, 2026)
Key message SlHair5 is a pivotal regulatory node downstream of the H–H4 module that coordinates epidermal differentiation with leaf morphogenesis and plant architecture through a dosage-sensitive transcriptional network and a reciprocal feedback loop. Abstract C2H2-type zinc finger proteins (C2H2 ZFPs) are essential regulators of plant development, yet the mechanisms governing their functional diversification and hierarchical organization in tomato ( Solanum lycopersicum ) remain largely elusive. In this study, we identified and characterized SlHair5 ( H5 ), a previously unassigned C2H2 ZFP that operates downstream of the established H–H4 regulatory module. H5 localizes to the nucleus, where its expression is indirectly activated by the H–H4 module. Functional characterization using CRISPR-Cas9-mediated knockout ( h5 -sko) and overexpression ( H5 -OX) lines demonstrated that H5 is a pivotal developmental regulatory node. At the cellular level, H5 promotes epidermal differentiation by modulating trichome density and stalk cell elongation in a type-specific manner. Intriguingly, H5 exhibits dosage-sensitive and non-linear regulatory effects; while trichome traits showed a relatively linear response to H5 levels, organ-level traits—such as leaf shape and plant height—displayed a threshold effect, with pronounced growth retardation and narrowed leaflets observed in H5 -OX lines. Transcriptomic profiling identified 569 differentially expressed genes, revealing that H5 orchestrates a broad network including regulators of trichome development ( JAZ4 and WRKY57 ), leaf morphogenesis ( Tf, GH3.15, BOPa , and CKX2 ), and stem elongation ( GT-26 and ER ). Furthermore, H5 exerts an indirect feedback control over H3 and H4 , thereby fine-tuning the ZFP regulatory hierarchy to maintain developmental homeostasis. Collectively, our findings establish H5 as a higher-order regulatory hub that coordinates cellular patterning with organismal architecture, providing critical insights into the transcriptional programs governing vegetative development in tomato.

The Tomato Juhwang Mutant Accumulates a High Level of β-Carotene and has a Long Shelf-Life - Seong-Yeop Kim; Seong-Min Kim; Jae-In Chun; Jung-Won Jung; Jae-Kwang Kim; Jihye An; Donghwa Chung; Jin-Ho Kang (Journal of Plant Biology, 2023)

Improvement of fluid penetration in soil by plasma blasting - Hyun-Sic Jang; In-Joon Baek; Jae-Yong Song; Geun-Chun Lee; Bo-An Jang (Geosciences Journal, 2022)

Tomato ARPC1 regulates trichome morphology and density and terpene biosynthesis - Jae-In Chun; Seong-Min Kim; Na-Rae Jeong; Sang Hee Kim; Choonkyun Jung; Jin-Ho Kang (Planta, 2022)

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Perfluorinated compounds in food simulants after migration from fluorocarbon resin-coated frying pans, baking utensils, and non-stick baking papers on the Korean market - Heeju Choi; In-Ae Bae; Jae Chun Choi; Se-Jong Park; MeeKyung Kim (Food Additives & Contaminants Part B-Surveillance, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Decreased Metabolism in the Posterior Medial Network with Concomitantly Increased Metabolism in the Anterior Temporal Network During Transient Global Amnesia - SangHak Yi; Young Ho Park; Jae-Won Jang; Jae-Sung Lim; In Kook Chun; SangYun Kim (Brain Topography, 2018)

Anoctamin 1 expression in the mouse auditory brainstem - Sang Jae Cho; Ji Hyun Jeon; Do Ill Chun; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2014)

Safety, functionality and stability tests of Ecklonia cava extract for dermal application - Jae-Suk Choi; Kyungyong Lee; Bo-Bae Lee; Yang-Chun Kim; Kwang Keun Cho; In Soon Choi (Toxicology and Environmental Health Sciences, 2014)

3,4,5-Trihydroxycinnamic acid inhibits lipopolysaccharide (LPS)-induced inflammation by Nrf2 activation in vitro and improves survival of mice in LPS-induced endotoxemia model in vivo - Jae-Won Lee; Chang Jun Bae; Yong-Jun Choi; Song-In Kim; Yong-Soo Kwon; Hee Jae Lee; Sung-Soo Kim; Wanjoo Chun (Molecular and Cellular Biochemistry, 2014)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Comparative analysis of expressed sequence tags (ESTs) of ginseng leaf - Myung Kyum Kim; Bum-Soo Lee; Jun-Gyo In; Hua Sun; Jae-Ho Yoon; Deok-Chun Yang (Plant Cell Reports, 2006)

Surfactin C inhibits the Lipopolysaccharide-induced Transcription of Interleukin-1β and Inducible Nitric Oxide Synthase and Nitric Oxide Production in Murine RAW 264.7 Cells - Mi-Hyun Hwang; Jong-Hwan Lim; Hyo-In Yun; Man-Hee Rhee; Jae-Youl Cho; Walter H. Hsu; Seung-Chun Park (Biotechnology Letters, 2005)

Changes in retinal neuronal populations in the DBA/2J mouse - Jung-Il Moon; In-Beom Kim; Jae-Sung Gwon; Myoung-Hee Park; Tae-Hoon Kang; Eun-Jin Lim; Kyu-Ryong Choi; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Isolation and characterization of a myo-inositol 1-phosphate synthase cDNA from developing sesame (Sesamum indicum L.) seeds: functional and differential expression, and salt-induced transcription during germination - Jae-An Chun; Un-Ho Jin; Jin-Woo Lee; Young-Byung Yi; Nam-In Hyung; Myung-Hwa Kang; Jae-Ho Pyee; Mi Suh; Churl-Whan Kang; Hong-Yeol Seo; Shin-Woo Lee; Chung-Han Chung (Planta, 2003)